Dari Mianzi Dan Lian Menuju Face: Dari Kearifan Lokal Cina Menuju Teori Kesantunan Yang Mendunia - Agung Pramujiono (Bina Nusantara University, 2012)
The politeness theory of Brown and Levinson (1987) about face is regarded as one very influential. In fact, it was rooted from Eastern local wisdom (ancient China), that is “mianzi” and “lian”. Mianzi represents social perceptions of one’s self-esteem built through lian as one’s morality. Politeness and limao have the same pragmatic basis but they can be perceived differently due to the varied cultural contexts underlying a speech community. In the intercultural pragmatics study, the differences should not form the sources of conflict but they should even be considered as varieties of pluralities about which the interactants should be understood in order that interpersonal communication activities can run harmoniously and can be avoided from all kinds of conflict and friction.